Comparing Clinical Outcomes of Five-Strand Hamstring Tendon Autograft and Quadrupled Hamstring Tendon Autograft for Single Bundle Anterior Cruciate Ligament Reconstruction in Filipinos - Albert Ian Villegas; Emmanuel Roy Mata; Jose Antonio San Juan; John Rey Go; Vick Roland Ladica (Philippine Journal of Orthopaedics)
Background: Anterior cruciate ligament (ACL) tears are common, especially in athletes, and are often treated with hamstring tendon autografts using a single-bundle technique. Graft diameter is crucial, with evidence showing that larger grafts reduce failure risk. Asian populations typically have smaller graft diameters. This study compares the clinical outcomes of the five-strand versus the quadrupled technique in a Filipino Asian population to assess potential benefits in graft thickness and knee stability.